Tooth ablation in Iron Age central Thailand: Evidence from the archaeological sites of Ban Mai Chaimongkol and Tha Kae. (30th July 2019) - Palefsky, Gina
Abstract: Tooth ablation is identified differentially among Iron Age inhabitants of the inland region of central Thailand at the archaeological sites of Ban Mai Chaimongkol and Tha Kae (ca. 2650–1450bp ). Analysis of the subsets of adult individuals with adequately preserved anterior dentition (Ban Mai Chaimongkol n  = 12; Tha Kae n  = 6) documents bilateral removal of the maxillary lateral incisors and canines at Ban Mai Chaimongkol and bilateral removal of the maxillary lateral incisors at Tha Kae, affecting 17% ( n  = 2) and 67% ( n  = 4) of observable individuals, respectively. Ablation was not associated with sex, age, mortuary features, or grave goods in this sample. Possible social significances of this practice are discussed in relation to skeletal evidence of tooth ablation elsewhere in Mainland Southeast Asia and archaeological contexts specific to central Thailand.